Characteristics And Risk Factors Of Diabetic Retinopathy In Multi-Ethnicity - Elsha Tiskya Azhary; Sitti Rukiah Syawal; Risna Rajab (Sean Institute, 2023)
Diabetic Retinopathy is one of the eye diseases most often experienced by Diabetes Mellitus sufferers. Diabetic Retinopathy damages blood vessels in the retina which can cause temporary or permanent blindness if treated too late. Differences in the prevalence of diabetic retinopathy between races can occur due to a combination of several things, including access to health facilities, genetic factors and other retinopathy risk factors such as ethnicity or race. Blacks and Hispanics have a much higher prevalence of diabetic retinopathy than whites and Asians. These differences were reduced when the analysis accounted for duration of diabetes, glycemic levels, and progression of diabetes, suggesting that these risk factors may partially explain the higher rates of retinopathy in blacks and Hispanics. Meanwhile, in Indonesia, according to the World Health Organization (WHO), Indonesia is fifth with the largest population of sufferers in the world, which is estimated to increase from 6.5 million to 20 million by 2030. Diabetic retinopathy is one of the eye diseases most often experienced by Diabetes Mellitus sufferers. Diabetic Retinopathy damages blood vessels in the retina which can cause temporary or permanent blindness if treated too late. Diabetic retinopathy accounts for 0.01% of causes of blindness, 0.04% of causes of moderate-severe visual impairment and overall visual impairment in Indonesia in 2020 is 13.2%.